Personal Pronouns in Biden’s Inaugural Speech: A Critical Discourse Perspective - Romadlani, Muhammad Masqotul Imam (Universitas Sanata Dharma, 2024)
This research primarily examines the first-person personal pronouns in political discourse, political speech in particular. This research aims to reveal how the pronoun I and we are exploited by the politician for the specific intention in political discourse. This research contextually investigates those personal pronouns and their inflectional forms based on the critical discourse analysis perspective, revealing the function and the purpose of producing a particular and an intentional personal pronoun to refer to specific addressee(s). That linguistic strategy in political context indicate the social and political relation between the speaker and the referents. The data in this research were taken from the script of Biden’s inaugural speech given in 2021. From 224 first-person personal pronouns, Biden produced the pronoun I and its inflectional forms 63 times or 28,1% and the pronoun we and its inflectional forms 161 times or 71,9 in percentage. Even though the plural form was identified as the most first-person personal pronoun produced by Biden, the occurrence of the pronoun we and its inflectional forms excluded Kamala Harris as his vice president. Biden exploited the first-person singular personal pronoun to express his gratitude, quality, positive image and persuasively to ingratiate the citizens. On the other hand, Biden expressed the pronoun we and its inflectional forms to establish a sense of national unity, togetherness to confront the challenges, and sharing responsibility. Personal pronouns no longer deal with language structure analysis only, but they are also employed to persuasively affect socio-political position, especially in a political context.